1999
DOI: 10.1038/sj.bjp.0702839
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal relaxing effects and β2 adrenoceptor selectivity of S1319, a novel sponge‐derived bronchodilator agent, in isolated guinea‐pig tissues

Abstract: 1 S1319 (4-hydroxy-7-[1-(1-hydroxy-2-methylamino)ethyl]-1,3-benzothiazol-2(3H)-one acetate), a novel non-catecholamine b-adrenoceptor agonist, has been compared with isoprenaline, salbutamol and formoterol for activity in vitro on a range of b-adrenoceptor containing preparations from guinea-pig. 2 S1319, like isoprenaline, salbutamol and formoterol, relaxed preparations of guinea-pig trachea (contracted by histamine) in a concentration-dependent manner. The relaxing activity of S1319 appeared to be more poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…In addition, functional experiments on guinea pig or other animal species in vivo or in vitro will be needed to confirm the selectivity of (Ϯ)-SPFF and its enantiomers, because the selectivity of agonists differs according to the animal species and experimental conditions used. 26) In agreement with the results of the study in vitro, in vivo experiments revealed subsequently that (Ϫ)-enantiomer exhibited more potent bronchodilation than (ϩ)-enantiomer. In particular, the potency of (Ϫ)-SPFF was equivalent to that of (Ϯ)-SPFF in the protective activity against a bronchospasm induced by histamine-acetylcholine aerosol, suggesting that the protective activity of (Ϯ)-SPFF might mainly reside in its (Ϫ)-enantiomer.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, functional experiments on guinea pig or other animal species in vivo or in vitro will be needed to confirm the selectivity of (Ϯ)-SPFF and its enantiomers, because the selectivity of agonists differs according to the animal species and experimental conditions used. 26) In agreement with the results of the study in vitro, in vivo experiments revealed subsequently that (Ϫ)-enantiomer exhibited more potent bronchodilation than (ϩ)-enantiomer. In particular, the potency of (Ϫ)-SPFF was equivalent to that of (Ϯ)-SPFF in the protective activity against a bronchospasm induced by histamine-acetylcholine aerosol, suggesting that the protective activity of (Ϯ)-SPFF might mainly reside in its (Ϫ)-enantiomer.…”
Section: Discussionsupporting
confidence: 79%
“…Generally, responses of the tracheal and bronchial smooth muscle tissues are similar due to common histoembryonic structure in many in vitro studies [8][9][10][11][12], so we tried to discuss the issue on this context. Neostigmine, as an anticholinesterase, has many side effects including bronchospasm, bradycardia, increase in secretions, accelerate peristalsis, residual block [5].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, S1319 (Fig. 1), a novel b 2 -selective agonist [22,23], inhibited the tryptase release at the same potency as isoproterenol and formoterol (Fig. 2) and the inhibitory effect of S1319 on the tryptase release was blocked by addition of propranolol (Table 2).…”
Section: The Effect Of S1319 On Ige-mediated Protein Tyrosine Phosphomentioning
confidence: 99%
“…2) and the inhibitory effect of S1319 on the tryptase release was blocked by addition of propranolol (Table 2). Although isoproterenol is a non-selective b-adrenoceptor agonist and propranolol is a non-selective b-adrenoceptor antagonist, that formoterol, albuterol and S1319, which are highly selective b 2 -adrenoceptor agonists [23], inhibited tryptase release suggests that the inhibitory activity is mediated through b 2 -adrenoceptors. Furthermore, RT-PCR analysis of b-adrenoceptor mRNA indicated that only b 2 -adrenoceptors are present in HCMC (Fig.…”
Section: The Effect Of S1319 On Ige-mediated Protein Tyrosine Phosphomentioning
confidence: 99%
See 1 more Smart Citation